Euchlorocystis marina sp. nov. (Oocystaceae, Trebouxiophyceae), a New Species of Green Algae from a Seawater Shrimp Culture Pond - Feng Li; Mingbiao Dong; Ning Zhang; Yulei Zhang; Qianru Li; Zuyuan Qian; Qingsheng Lian; Jiansen Luo; Xianghu Huang; Changling Li (Diversity, 2022)
Oocystaceae is a cosmopolitan family of green algae with distinct morphology and ultrastructure. Most of the reported species in this family are freshwater species, and there are few marine species reported. In this study, we describe a new marine species of Oocystaceae, Euchlorocystis marina sp. nov. based on material collected from a seawater shrimp culture pond in Zhanjiang, China. An integrative approach, including phylogenetic analyses of 18S rDNA, light microscopy, and transmission electron microscopy, was used for the taxonomic study of the strains. Morphological observation results showed that it has a multilayer thick cell wall, multiple pyrenoids in the chloroplast, and usually 2–16 cells forming a colony in the extended mother cell wall. These features are morphologically similar to the genus Euchlorocystis and are distinguished from other taxa of the family Oocystaceae. The 18S rDNA phylogenetic trees revealed that the strains and Euchlorocystis subsalina formed an independent clade in Oocystaceae with robust support. However, horseshoe-shaped chloroplasts and rounder cells morphologically distinguished it from Euchlorocystis subsalina. Apart from the morphology, the direct comparison of sequences also supported that they were distinct species. The discovery and description of the new species enriches the marine species record of the family Oocystaceae.